Zeke Meeks vs. the horrifying TV-Turnoff Week - Green, D. L. (Debra L.) (Zeke Meeks, 2012)
It is Television-Turnoff Week, and Zeke and his friends are wondering what they will do with their time without their favorite programs and videogames.